Dr Wan Isni Sofiah develops algorithm for saving battery usage in sensor nodes - Nur Hartini, Mohd Hatta (2020)
Kuantan, 26 October 2020 - Batteries are an important element for wireless sensor nodes to perform the process of sending and transmitting data.